2016
DOI: 10.1111/cga.12143
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction that does not have an influence on the birthweight of the offspring induces morphological changes in kidneys reminiscent of phenotypes exhibited by intrauterine growth retardation rats

Abstract: Severe restriction of maternal protein intake to 6-8% protein diet results in intrauterine growth retardation (IUGR), low birthweight and high risk of metabolic syndrome in the adult life of the offspring. However, little information is available on the effects of maternal protein restriction on offspring under the conditions that does not have an influence on their birthweight of the offspring,. In the present study, pregnant rats were kept on a diet consisting of either 9% (low-protein, Lp rats) or 18% (norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…A consistent finding in rats (Woodall et al, 1996 ; McMullen and Langley-Evans, 2005 ) and mice (Kawamura et al, 2007 ) is that fetuses exposed to undernutrition or a low-protein diet during the first half of pregnancy or throughout pregnancy are significantly smaller than normal. Even a less severe low-protein diet that does not induce IUGR leads to similar alterations in kidney morphology, with a reduction in the number of glomeruli and glomerular necrosis (Yuasa et al, 2016 ). The other animal model used for IUGR is the artery ligation model, which mimics an acute situation and not only diminishes the nutrient supply but also leads to oxygen deprivation (Janot et al, 2014 ).…”
Section: Animal Models Of Iugrmentioning
confidence: 99%
“…A consistent finding in rats (Woodall et al, 1996 ; McMullen and Langley-Evans, 2005 ) and mice (Kawamura et al, 2007 ) is that fetuses exposed to undernutrition or a low-protein diet during the first half of pregnancy or throughout pregnancy are significantly smaller than normal. Even a less severe low-protein diet that does not induce IUGR leads to similar alterations in kidney morphology, with a reduction in the number of glomeruli and glomerular necrosis (Yuasa et al, 2016 ). The other animal model used for IUGR is the artery ligation model, which mimics an acute situation and not only diminishes the nutrient supply but also leads to oxygen deprivation (Janot et al, 2014 ).…”
Section: Animal Models Of Iugrmentioning
confidence: 99%
“…Maternal protein restriction is able to promote growth restriction at birth followed by the subsequent catch-up growth ( Ozanne and Hales, 2004 ; Ozanne and Nicholas Hales, 2005 ). However, several studies with pregnant rats fed a low-protein diet reported pups with reduced body weight at birth which was maintained up to one year of ag ( Zeman, 1967 ; Zambrano et al, 2005 ; Hoppe et al, 2007 ; Fetoui et al, 2009 ; Qasem et al, 2016 ; Yuasa et al, 2016 ). Consistent with these results, we observed lower body weight of the male offspring at birth after maternal protein restriction and at all analyzed ages.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal protein malnutrition can have effects on offspring morphology, physiology and behavior. Variations in the phenotype of the offspring are induced by feeding pregnant dams a diet with a moderate reduction in protein (Yuasa et al, 2016). Some studies have shown that low-protein diets during pregnancy influence body weight, blood pressure and metabolic and intake regulatory systems in offspring (Jahan-Mihan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%